2022
DOI: 10.3390/molecules27082423
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Testing of Antioxidant and Protective Effect of Hyalurosomes Loading Extract Rich in Rosmarinic Acid Biotechnologically Produced from Lavandula angustifolia Miller

Abstract: Culture of plant cells or tissues is a scalable, sustainable, and environmentally friendly approach to obtain extracts and secondary metabolites of uniform quality that can be continuously supplied in controlled conditions, independent of geographical and seasonal variations, environmental factors, and negative biological influences. In addition, tissues and cells can be extracted/obtained from the by-products of other industrial cultivations such as that of Lavandula angustifolia Miller (L. angustifolia), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The extraction yield was not high, as it was ~7%. The total phenolic content of the extract was 23.8 mg gallic acid equivalent/g of dry extract, and the antioxidant activity was 4.3 mg trolox equivalent/g of dry extract [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction yield was not high, as it was ~7%. The total phenolic content of the extract was 23.8 mg gallic acid equivalent/g of dry extract, and the antioxidant activity was 4.3 mg trolox equivalent/g of dry extract [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to its unique gelling properties, gelatin is one of the most popular protein biopolymers, widely used in food, pharmaceutical and cosmetic fields [ 6 , 17 ]. Previous results underlined that the modification of nutriosomes with the addition of gelatin or other polymers can further improve their performances [ 18 ]. In a recent work, Perra et al (2022) also demonstrated that gelatin can be effectively added to liposomes and nutriosomes and they improve the effect of the grape extract on the stimulated proliferation of Limosilactobacillus reuteri , even at lower concentrations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, several studies involving RA in modified systems has been reported [44][45][46][47][48]. For instance, Perra and colleagues developed hyalurosomes loaded with an extract rich in RA and proved, in vitro, its protection against oxidative stress in skin fibroblasts [49].…”
Section: Discussionmentioning
confidence: 99%
“…Lavender (Lavandula angustifolia Mill.) is one of the most popular aromatic plants in the Lamiaceae family with origin in the Mediterranean region and is cultivated worldwide for medicinal and commercial purposes [1,2]. Lavandula angustifolia (L. angustifolia) has great economic values as an essential oil-producing plant.…”
Section: Introductionmentioning
confidence: 99%
“…Te chemical composition of the EO difers according to the extraction technique [5,10]. However, essential oil from L. angustifolia is composed of various constituents, including esters: linalyl acetate, lavandulyl acetate, and geranyl acetate; alcohols: linalool, α-terpineol, and terpinen-4-ol; sesquiterpenes: β-caryophyllene; and monoterpene: cisβ-ocimene [2,4,[10][11][12][13]. Te greater proportion is linalyl acetate and linalool which are considered active constituents, but linalool is considered one of the most examined odorant molecules [14].…”
Section: Introductionmentioning
confidence: 99%